How the selfish brain organizes its supply and demand - Hitze, Britta; Hubold, Christian; Van Dyken, Regina; Schlichting, Kristin; Lehnert, Hendrik; Entringer, Sonja; Peters, Achim (Frontiers in Neuroenergetics, 2010)
During acute mental stress, the energy supply to the human brain increases by 12%. To determine how the brain controls this demand for energy, 40 healthy young men participated in two sessions (stress induced by the Trier Social Stress Test and non-stress intervention). Subjects were randomly assigned to four different experimental groups according to the energy provided after stress intervention (rich buffet, meager salad, dextrose-infusion and lactate-infusion). Blood samples were frequently taken and subjects rated their autonomic and neuroglycopenic symptoms by standard questionnaires. We found that stress increased carbohydrate intake from a rich buffet by 34 g (from 149±13 in the non-stress session to 183±16 g in the stress session; P<0.05). While these stress-extra carbohydrates increased blood glucose concentrations, they did not increase serum insulin concentrations. The ability to suppress insulin secretion was found to be linked to the sympatho-adrenal stress-response. Social stress increased concentrations of epinephrine 72% (18.3±1.3 vs. 31.5±5.8 pg/ml; P<0.05), norepinephrine 148% (242.9±22.9 vs. 601.1±76.2 pg/ml; P<0.01), ACTH 184% (14.0±1.3 vs. 39.8±7.7 pmol/L; P<0.05), cortisol 131% (5.4±0.5 vs. 12.4±1.3 µg/dl; P<0.01) and autonomic symptoms 137% (0.7±0.3 vs. 1.7±0.6; P<0.05). Exogenous energy supply (regardless of its character, i.e. rich buffet or energy infusions) was shown to counteract a neuroglycopenic state that developed during stress. Exogenous energy did not dampen the sympatho-adrenal stress-responses. We conclude that the brain under stressful conditions demands for energy from the body by using a mechanism, which we refer to as ‘cerebral insulin suppression’ and in so doing it can satisfy its excessive needs.